OPTIMALISASI PENGELOLAAN KEUANGAN KOPERASI MAJELIS TA’LIM AN NISA (KOPMATA) UNTUK PEMBERDAYAAN EKONOMI MASYARAKAT - Novianti, Windi (ABISATYA DINAMIKA ISWARA PUBLISHING, 2023)
Cooperatives are a form of business entity that continues to be developed in Indonesia. It is hoped that this cooperative will continue to develop because it is considered to be in accordance with the character of the Indonesian nation, namely Gotong Royong. The independence of cooperatives is highly expected so that cooperatives become businesses that are able to stand alone in carrying out their business activities independently, able to earn profits so that they can maintain the continuity of their business and improve the welfare of cooperative members. Financial management is important for cooperative administrators to pay attention to. Financial management responsibilities start from preparing budgets to preparing financial reports. For the development and development of cooperatives as business entities which also act as drivers of the people's economy, cooperatives must be managed with open, transparent and accountable principles. This activity aims to ensure that managers can understand that managing finances needs to be done, so that it is useful in overcoming the problems currently being faced in managing cooperative finances. This activity is carried out by conducting a literature study, determining the location, determining the implementation time and duration of the activity, determining and preparing material, delivering material in the form of material and illustrations regarding financial management. The result of this activity is that cooperative financial managers can find out how to manage finances by making financial reports. The conclusion from this activity is that training in managing finances is a very important activity, it is hoped that managers can manage cooperative finances well.